PTH-352 Selective extra levator versus standard abdominoperineal resection - experience from a tertiary care centre. (22nd June 2015) - Pai, V; Vallam, KC; Tamhankar, A; Desouza, A; Arya, S; Patil, P; Engineer, R; Saklani, AP
Abstract : Introduction: Comparison of Extralevator abdomino perineal resection [ELAPER] with conventional Abdominoperineal resection[APER] with regard to short term oncological and clinical outcomes. Method: Patients with low rectal cancer who underwent abdomino perineal resection in TMH during the time period from July 2013 to January 2015 were included. Decision to perform ELAPER was based on levator involvement, with APER being performed in those with levators free. Short term oncological outcomescomparedincluded CRM, tumour site perforation [TSP] and number of nodes dissected. Clinical outcomes compared included post-operative perineal wound complications, need for plastic reconstruction and hospital stay. Results: One hundred twenty patients with low rectal cancers underwent abdomino perineal resection during the defined study period. Out of these forty had undergone ELAPER. Both groups were comparable in the baseline characteristics except levator involvement which was significantly higher in ELAPER group. CRM involvement was seen in 8.75% with APER compared to 5% with ELAPER. Median blood loss was 400 ml with APER compared to 500 ml with ELAPER. Plastic reconstruction was required in 5% of APR and 17.5% of ELAPER. Conclusion: Selective use of ELAPER is warranted in cases of low rectal cancer particularly when levators are involved by the tumour on MRI. Disclosure of interest: None Declared.